Modeling and simulation of automotive wiper noise and vibration using finite element method - Awang, I. M.; C., Y. Leong; Abu Bakar, Abd. Rahim; Abdul Ghani, Badri; Abd. Rahman, Roslan; Md. Zain, Mohd. Zarhamdy (2008)
As modern passenger cars become increasingly quieter, wiper operation vibration and noise become more noticeable. As a result of the market information analysis, most complaints about the wiper concern operation noise. Wiper vibration and noise is classified into three main categories namely, squeal noise, chattering, and reversal noise. Squeal noise is a high-frequency vibration of about 1000 Hz. Chattering noise is a low-frequency vibration of 100Hz or less and reversal noise is an impact sound with a frequency of 500 Hz or less produced when the wiper reverses. This paper presents numerical studies on noise and vibration of an automotive wiper blade. A 3-dimensional (3D) finite element (FE) model of a wiper blade assembly is developed and then validated at the component level using modal analysis. Complex eigenvalue analysis available in ABAQUS is employed to determine stability of the wiper blade assembly. It is found that predicted results from complex eigenvalue analysis are fairly close to those generated in the experiment.